2021
DOI: 10.1007/s00404-020-05905-8
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preserving management of early endometrial cancer in a patient cohort at the department of women’s health at the university of Tuebingen

Abstract: Purpose To investigate the oncologic and reproductive outcome of a conservative treatment with progestin agents in early-stage grade 1 endometrial cancer (G1EC), grade 2 endometrial cancer (G2EC) or complex atypical hyperplasia (CAH) in young premenopausal women. Methods Women treated for early-stage endometrial cancer or atypical hyperplasia of the endometrium with a conservative therapy between 2006 and 2018 were enrolled in this retrospective analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The study selection process is displayed in Figure 1 . After the evaluation of the full texts, 22 papers that met the abovementioned inclusion criteria [ 23 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] were included in the present systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…The study selection process is displayed in Figure 1 . After the evaluation of the full texts, 22 papers that met the abovementioned inclusion criteria [ 23 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] were included in the present systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Among 168 potentially relevant records, six studies with a total of 124 participants were included in the systematic review and shown in Table 1 (9)(10)(11)(12)(13)(14). Four eligible articles were retrospective studies (9,10,13), whereas two articles were prospective trials (9,10).…”
Section: Resultsmentioning
confidence: 99%
“…FST consisted of dydrogesterone 10 mg for 3 months, but she did not respond to the treatment: her disease remained stable after a follow-up (FU) time of 6 months. The woman did not manage to conceive (12). Falcone et al examined 23 patients with intramucosal, G2 endometrioid EC with a mean FU duration of 35 months (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effectiveness of the fertility-spared treatment has now been widely recognized, the overall CR rate of conservative treatment is reported to fluctuate from 50.0 to 90.0% ( 13 15 ). Despite the different use of progestins and hysteroscopy, a center reported that even under the same treatment and histological type, the CR rate was only 40.0% in patients who were diagnosed as grade 1 endometrioid adenocarcinoma with minimal myometrial infiltration ( 16 ).…”
Section: The Conservative Treatment Of Ecmentioning
confidence: 99%